Analysing, Sustaining and Piloting Innovation: A “ASPI” Model - Peraya, Daniel; Jaccaz, Bérénice; Masiello, Italo; Armitage, Susan; Yip, Hennie (Proceedings of the International Conference on Networked Learning, 2004)
This paper proposes a framework, both theoretical and practical, that attempts to provide information and scaffolding mainly to university staff but also to policy makers who currently face the initiative of implementing innovation, in all its forms, in the education system. It aims at helping all the different actors, from university managers to university lecturers, involved in the teaching and learning process to answer the following questions: “How do I analyse, guide, and sustain innovation in Higher Education?”, “What kind of information do I need at each stage of the innovation process to make decisions that serve my goals?”, “How do I process the data generated?”, and “How do I feed the results back into the process?”